The Genetic Architecture of Arabidopsis thaliana in Response to Native Non-Pathogenic Bacterial Species Revealed by Genome-Wide Association Mapping in Field Conditions - Daniela Ramírez-Sánchez; Rémi Duflos; Chrystel Gibelin-Viala; Rémy Zamar; Fabienne Vailleau; Fabrice Roux (Phytobiomes Journal)
Non-pathogenic bacteria can substantially contribute to plant health by mobilizing and supplying nutrients, providing protection against pathogens, and alleviating abiotic stresses. However, the number of genome-wide association studies reporting the genetic architecture of the response to individual members of the beneficial microbiota remains limited. In this study, we established a genome-wide association study under field conditions to estimate the level of genetic variation and the underlying genetic architecture among 162 accessions of Arabidopsis thaliana originating from 54 natural populations in the southwest of France in response to 13 strains of seven of the most abundant and prevalent non-pathogenic bacterial species isolated from the leaf compartment of A. thaliana in the same geographical region. Using a high-throughput phenotyping methodology to score vegetative growth-related traits, extensive genetic variation was detected among A. thaliana accessions in response to these leaf bacteria, at both the species and strain levels. The presence of crossing reaction norms between each strain and the mock treatment indicates that declaring a strain as a plant growth-promoting bacterium is highly dependent on the host genotype tested. In line with the strong genotype-by-genotype interactions, we detected a complex and highly flexible genetic architecture between the 13 strains. Finally, the candidate genes underlying the quantitative trait loci revealed significant enrichment in several biological pathways, including cell, secondary metabolism, signaling, and transport. Altogether, plant innate immunity appears as a significant source of natural genetic variation in plant–microbiota interactions and opens new avenues for better understanding the ecologically relevant molecular dialog during plant–microbiota interactions. [Figure: see text] Copyright © 2024 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.